2018
DOI: 10.1186/s40703-018-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Loading rate conditions and specimen size effect on strength and deformability of rock materials under uniaxial compression

Abstract: Determination of the uniaxial compressive strength (UCS), one of the most crucial inputs in rock engineering design works is detailed in different standards and suggestions by the International Society for Rock Mechanics and Rock Engineering (ISRM). The relevant standards and suggestions include some statements to select appropriate values of different parameters like geometry, size and loading rate. As ideal geometry of the UCS test specimens, length to diameter (L/D) ratio of the cylindrical specimens is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…By conducting numerical simulations, the researchers explored the relationship between these variables. The results indicate that an increase in confining stress leads to a higher peak strength of rocks at failure, which aligns with previous research [29], [30]. Furthermore, the study reveals that the effect of incremental displacement on the ultimate strength of rock diminishes as the displacement increases.…”
Section: Discussionsupporting
confidence: 91%
“…By conducting numerical simulations, the researchers explored the relationship between these variables. The results indicate that an increase in confining stress leads to a higher peak strength of rocks at failure, which aligns with previous research [29], [30]. Furthermore, the study reveals that the effect of incremental displacement on the ultimate strength of rock diminishes as the displacement increases.…”
Section: Discussionsupporting
confidence: 91%
“…The thermal strains can make significant damages as it is a well-known property of the brittle cementitious materials (Heidari-Rarani et al, 2014;Khan et al, 2020;Shang and Lu, 2014;Kaya et al, 2016;Keskin et al, 2017). Since the main reason for the increase in the ductility is the improvement in the crack propagation resistivity, it is an estimated result to have an improvement against the repeated strains of thermal cycles with an increase in the ductility (Groeneveld et al 2018;Das et al, 2020;Komurlu, 2018). In a study carried out by Komurlu (2020), the same thermoset polymer additive with that used in this study was investigated to determine its effect on the ductility of the cement grouts and it was reported that the additive notably improves the ductility and the energy absorption capacities of the grout mixes.…”
Section: Discussionmentioning
confidence: 99%
“…Percebeu-se que o aumento da velocidade de carregamento gerou maiores valores de tensão de escoamento e de resistência máxima. Komurlu (2018) avaliou 5 tipos diferentes de rocha, uma pasta de cimento e uma argamassa de cimento e areia quanto a influência da taxa de deformação na resistência à compressão, módulo de elasticidade e fragilidade. O autor observou que os três parâmetros sofreram um aumento com o incremento da velocidade de deformação.…”
Section: Contextualizaçãounclassified